Making agroecology work in Zimbabwe - why joined-up government matters: Policy brief - Marenya, Paswel; Chiduwa, Mazvita Sheila; Ngoma, Hambulo; Chipindu, Lovemore; Nohayi, Ngowenani; Chimonyo, Vimbayi Grace Petrova (CIMMYT, 2025)
Efforts to promote agroecological transitions in Zimbabwe are constrained by challenges in policy and institutional coordination and not by unambitious policy intentions. Several policies and strategies refer to sustainability and resilience goals: yet implementation lags, leading to large intention-implementation gaps. This raises the question, why? This policy brief synthesizes evidence from literature review and a national stakeholder influence-interest mapping exercise published here1 elucidating on how to close the intention-implementation gaps. The findings reveal that the large intention-implementation gap can be closed by developing an overarching agroecology theory of change and a “one-government” approach that enhances cross sectoral coordination and accountability.